Development of Augmented Reality Based Interactive Science Multimedia with the Problem Based Learning Model to Enhance the Higher Order Thinking Skills Students - Feri Apriansah; Endang Widi Winarni; Endina Putri Purwandari; Neza Agusdianita; Abdul Muktadir; Yusnia Yusnia; Debi Heryanto (IJIS Edu : Indonesian Journal of Integrated Science Education, 2026)
This study aims to develop and determine the validity, practicality, and effectiveness of Augmented Reality (AR)-based interactive science multimedia integrated with the Problem Based Learning (PBL) model to enhance the Higher-Order Thinking Skills (HOTS) of fifth-grade elementary school students on the topic of the human circulatory system. The research employed the Research and Development (R&D) approach with the ADDIE model, comprising the analysis, design, development, implementation, and evaluation phases. It was conducted at SDIT IQRA' 1 Bengkulu City in the even semester of the 2025/2026 academic year, involving 28 students in the limited trial and 28 students in the field trial. Data were collected through expert validation sheets, teacher and student response questionnaires, and HOTS tests, then analyzed using Aiken's V for content validity, percentage techniques for practicality, and N-Gain for effectiveness. The developed multimedia obtained an Aiken's V index of 1.00 (very valid) for the material, language, and graphic aspects, with 100% inter-rater agreement. Teacher responses reached 100% (very good) and student responses 97.38% (very practical). The effectiveness test yielded an average N-Gain of 0.75 (high), with the analysis (C4), evaluation (C5), and creation (C6) aspects scoring 0.79, 0.81, and 0.64 respectively. These findings indicate that AR-based interactive science multimedia integrated with the PBL model is valid, practical, and effective for enhancing students' HOTS and supporting 21st-century science learning.